2010
DOI: 10.2136/sssaj2009.0185
|View full text |Cite
|
Sign up to set email alerts
|

Unweathered Wood Biochar Impact on Nitrous Oxide Emissions from a Bovine‐Urine‐Amended Pasture Soil

Abstract: Low‐temperature pyrolysis of biomass produces a product known as biochar The incorporation of this material into the soil has been advocated as a C sequestration method. Biochar also has the potential to influence the soil N cycle by altering nitrification rates and by adsorbing or NH3 Biochar can be incorporated into the soil during renovation of intensively managed pasture soils. These managed pastures are a significant source of N2O, a greenhouse gas, produced in ruminant urine patches. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(169 citation statements)
references
References 37 publications
10
148
3
3
Order By: Relevance
“…Wang et al (2012) reported that biochar application decreased N 2 O emissions up to 54 and 53 % during rice and wheat seasons. However, Clough et al (2010) and Kristiina et al (2011) found that biochar application had no effect on N 2 O emissions. Zhang et al (2012) reported that biochar amendment (20 t ha -1 ) in a Chinese paddy soil increased GWP by 39 % in the first growing cycle; however, the overall GWP decreased (7-18 %) in the second consecutive growing season.…”
Section: Discussionmentioning
confidence: 96%
“…Wang et al (2012) reported that biochar application decreased N 2 O emissions up to 54 and 53 % during rice and wheat seasons. However, Clough et al (2010) and Kristiina et al (2011) found that biochar application had no effect on N 2 O emissions. Zhang et al (2012) reported that biochar amendment (20 t ha -1 ) in a Chinese paddy soil increased GWP by 39 % in the first growing cycle; however, the overall GWP decreased (7-18 %) in the second consecutive growing season.…”
Section: Discussionmentioning
confidence: 96%
“…To date, several studies have shown that the addition of biochar to soils can mitigate N 2 O emissions in situ from soybean and grass ecosystems [48], following ruminant urine deposition [49], in wheat plots [50] and during laboratory or greenhouse incubations under various conditions [8,9,47,[51][52][53][54][55][56][57][58][59][60][61] while other studies have found no differences or even increases in cumulative N 2 O emissions after biochar addition [61][62][63].…”
Section: Mitigation Of Nitrous Oxide Emissions Using Biocharmentioning
confidence: 99%
“…Some has shown no effect 13 and some that biochar increased soil N 2 O emissions. 14 In addition to the uncertain effect of biochar on N 2 O emission, the factors and mechanisms of the influence of biochar on N 2 O remain unclear due to the complex N 2 O formation pathways. N 2 O can be produced from several closely related biological processes in soil, including nitrification, nitrifier denitrification, denitrification, codenitrification, dissimilatory nitrate reduction to ammonia, nitrate assimilation, and chemodenitrification, among which nitrification and denitrification are predominant.…”
Section: ■ Introductionmentioning
confidence: 99%